Comparative study on removal of monodyes by using Ni-Al layered double hydroxides - Dao, T. T. U.; Nguyen, T. H. T.; Phan, T. T. Q.; Do, T. S.; Vo, Dai-Viet N.; Tien, N. A. (IOP Publishing, 2020)
The toxic and carcinogenic effluents discharged from the textile and garment industry represent a major concern to the environment and public health. Treatment technologies for these effluents to reduce toxicity and dye concentration are therefore crucial. The objective of this study was to focus on eliminating four monoazo dyes including Congo (CR), Methyl orange (MO), Methylene blue (MB) and Crystal violet (CV) using adsorbents, Ni/Al LDHs. The results proved that Ni/Al LDHs exhibit excellent adsorption capacity on anionic dyes (CR, MO) instead of cationic dyes (CV, MB). The maximum adsorption capacity of Methyl Orange on Ni/Al LDHs was found to be 93.517 mg/g and Congo red at 87.975 mg/g. In addition, the study of leaching test of adsorbents show stable synthetic materials in aqueous media. The analyses mentioned above indicates that Ni/Al LDHs may be a promising adsorbent to remove anion dyes from aqueous media.